Pengaruh Media Video Pembelajaran Terhadap Hasil Belajar IPA Materi Siklus Air Kelas V SD Negeri Lontar II Surabaya - Ari Mawanto (Departement of Mathematics Education, 2022)
This study aims to determine the effect of instructional video media on science learning outcomes in the water cycle material for class V SD Negeri Lontar II Surabaya, as well as to determine student responses related to the use of video in the teaching and learning process. This type of research is experimental research using a quantitative approach. Data collection in this study used several techniques, namely observation, interviews, documentation studies and questionnaires. Furthermore, the collected data were analyzed using a statistical approach with the calculation of the percentage and Product Moment correlation. The use of science learning videos is generally in great demand by all students of SD Negeri Lontar II Surabaya, as the results of research conducted on 21 respondents who became the research sample turned out to be 80.95% who said they strongly agreed that water cycle learning was carried out using learning videos. students by using learning videos on 21 respondents who were used as research samples, it turned out that learning outcomes reached an average value of 86.43. Based on the calculation of the data associated with the correlation index number (r) product moment is between 0.70-0.90 which means it is in the high correlation category, while the results of the calculation of the correlation between the use of video and student learning outcomes is 0.76 which means it has a relationship tall one. So it can be concluded that there is an Influence of Learning Video Media on Science Learning Outcomes for Class V Water Cycle Materials at SD Negeri Lontar II Surabaya